River Response to Melting Cryosphere Since Late Quaternary in the Pir Panjal Range of NW Himalaya - Dar, Reyaz Ahmad; Murtaza, Khalid Omar; Paul, Omar Jaan; Nisa, Azra Un; Akhter, Nida; Dar, Farooq Ahmad; Mir, Riyaz Ahmad (Frontiers in Water, 2022)
Rambiara River basin, a sub-basin of the Upper Indus, is dotted with fluvial and glacial geomorphic landforms. The presence of a large number of glacial landforms like moraines, cirques, aretes, U-shaped valleys, etc. reflects the enormous erosive power of the past glaciers. During the Last Glacial Maximum (LGM), glaciers on average were 200m thick and extended more than 10km from the present-day cirque marks. Rock glaciers outnumber the clean glaciers that cover an area of 0.22 km² and 1.25 km² respectively in the basin. Glacial lakes are the prominent features in the higher reaches of the basin and occupy an area ranging from 0.01-0.70 km². Downstream, the river is characterized by large channel width, anomalous sinuosity, braided pattern, and the presence of unpaired fluvial terraces. The large channel width depicts the enormous discharge from the glacial- and snow-melt during the Late Pleistocene when glaciers covered most of the Pir Panjal. After LGM, the glacier cover and the river discharge significantly decreased as highlighted by a large number of braided bars and the narrow stream to which the river is reduced. The warming trends observed across the Himalayas encompassing the Pir Panjal Range since the last century has further contributed significantly to the glacier recession in the basin.